Clinical outcomes of second‐generation tyrosine kinase inhibitors versus imatinib in older patients with CML. Issue 3 (23rd November 2022) - Ono, Takaaki; Takahashi, Naoto; Kizaki, Masahiro; Kawaguchi, Tatsuya; Suzuki, Ritsuro; Yamamoto, Kazuhito; Ohnishi, Kazunori; Naoe, Tomoki; Matsumura, Itaru
Abstract: Age and comorbidities are important factors to be considered in the selection of tyrosine kinase inhibitors (TKIs) for first‐line treatment in patients with chronic myeloid leukemia in chronic phase (CML‐CP). However, it is yet unclear whether TKI selection, particularly, imatinib versus second‐generation TKIs (2GTKIs), impacts treatment outcomes in the clinical practice. To address this, we compared the clinical outcomes of prospectively registered 452 patients with CML‐CP treated with imatinib and 2GTKIs, taking into consideration their age and/or comorbidities. A total of 136 patients (30.1%) were classified into an older cohort (≥65 years) and 316 (69.9%) into a younger cohort (18‐64 years). The TKI selection did not vary based on age (70.6% received 2GTKIs in the younger cohort and 66.2% in the older cohort). The median follow‐up period was 5.4 years. Treatment responses including the cumulative incidence of deep molecular response (BCR‐ABL1 international scale ≤0.0032%) at any time were similar between the two age cohorts regardless of the type of TKI. The 5‐year overall survival (OS) in the older cohort was lower than that in the younger cohort (95.9% vs 83.8%; p  < 0.0001), whereas the 5‐year OS in patients treated with 2GTKIs was not influenced by age factors and comorbidities. Therefore, our results suggest that the selection of 2GTKIs as first‐line treatment is an effective option for both younger and older CML‐CP patients with or without comorbidities. This trial was registered at UMIN‐CTR as 00003581. Abstract : The overall survival in patients with chronic myeloid leukemia in chronic phase (CML‐CP) who treated with second‐generation tyrosine kinase inhibitors (2GTKIs) was not influenced by age factors, which was not observed in patients on imatinib. 2GTKI as first‐line treatment is a considerable option for both elderly and younger patients with CML‐CP.